1976
DOI: 10.1093/oxfordjournals.aje.a112287
|View full text |Cite
|
Sign up to set email alerts
|

Providencia Stuartii, a Hospital Pathogen: Potential Factors for Its Emergence and Transmission

Abstract: The emergence of Providencia stuartii as a hospital pathogen in a burn unit was demonstrated by routine infection surveillance. The organism was initially recognized in a burn wound and subsequently in urine or sputum. Compared to controls, those patients harboring P. stuartii were similar in age and percentage of body surface burned and were more likely to have been in one of the two burn unit rooms, (p less than 0.02). Infection with P. stuartii was independent of duration in the Intensive Care Unit or Burn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The bacteria of the genus Providencia are gram negative and rod shaped and belong to the family Enterobacteriaceae. They have been reported to cause infections of the intestinal tract (1, 12) and the urinary tract (6, 15) and have been implicated in the establishment of nosocomial infections (3,7,12,14,16,17).Our interest in these bacteria has led us to establish serotyping schemes, and we have serotyped numerous isolates ofeach species during the course of other investigations (8)(9)(10) (4). A collection of 630 P. stuartii isolates included both urea-negative and ureapositive isolates from different hospitals as described previously (10), and the 537 P. rettgeri isolates in our collection were mostly those that were described earlier (9) and included isolates from different hospitals, public health laboratories, animals, and polluted water.…”
mentioning
confidence: 99%
“…The bacteria of the genus Providencia are gram negative and rod shaped and belong to the family Enterobacteriaceae. They have been reported to cause infections of the intestinal tract (1, 12) and the urinary tract (6, 15) and have been implicated in the establishment of nosocomial infections (3,7,12,14,16,17).Our interest in these bacteria has led us to establish serotyping schemes, and we have serotyped numerous isolates ofeach species during the course of other investigations (8)(9)(10) (4). A collection of 630 P. stuartii isolates included both urea-negative and ureapositive isolates from different hospitals as described previously (10), and the 537 P. rettgeri isolates in our collection were mostly those that were described earlier (9) and included isolates from different hospitals, public health laboratories, animals, and polluted water.…”
mentioning
confidence: 99%
“…In the past decades, Gram-negative organisms have emerged as the most common etiologic agents of invasive infections, and antibiotic-resistant organisms have increasingly been isolated in burn units (10). However, very few studies have reported endemic or epidemic situations due to P. stuartii in these wards (11,41,53). Most patients of this study suffered from severe burn injury (mean TBSA, greater than 40%) and thus exhibited risk factors for acquiring multidrug-resistant bacteria, i.e., antibiotic receipt, extended duration of hospitalization, and invasive procedures, together with immunosuppression induced by the burn injury (10,50).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this opportunistic pathogen is essentially responsible for urinary tract infections, particularly in long-term care populations (33). P. stuartii is intrinsically resistant to aminopenicillins and narrow-spectrum cephalosporins due to a chromosomally encoded Ambler class C cephalosporinase (12,22,53). Overexpression of AmpC usually confers to this species a low-level resistance to broad-spectrum cephalosporins such as ceftazidime (12).…”
mentioning
confidence: 99%
“…The development of bacterial resistance to silver nitrate (Cason et al 1966;Cason and Lowburry 1968) prompted a change in formulation and the use of silver sulphadiazine -a combination of silver and sulphonamide (Fox 1968;Modax and Fox 1974;Modak et al 1988). In the 1970s, outbreaks of burn wound infection or colonization by Gram-negative isolates resistant to ionic silver and silver sulphadiazine were reported for a number of bacteria; in Enterobacter cloacae (Gayle et al 1978), Providencia stuartii (Wenzel et al 1976), Pseudomonas aeruginosa (Bridges et al 1979) and Salmonella typhimurium (Mchugh et al 1975). Bacterial resistance to silver sulphadiazine developed rapidly mainly because of the antibiotic component (Klasen 2000).…”
Section: Bacterial Resistance To Silver and Ag-npmentioning
confidence: 99%
“…In vitro evidence of bacterial resistance to ionic silver Exposure to silver may contribute to the selection of bacteria that are intrinsically resistant to silver (Wenzel et al 1976;Bridges and Lowburry 1977;Haefeli et al 1984;Silver 2003;Davis et al 2005). Emerging silver-resistance from environmental bacterial isolates has been documented in Enterobacteriaceae (Hendry et al 1979;Kaur and Vadehra 1986;Trevors 1989, 1990) and in Acinetobacter baumanii (Deshpande and Chopade 1994) under experimental conditions.…”
Section: Bacterial Resistance To Silver and Ag-npmentioning
confidence: 99%